Proposta de um sistema de entrega com veículos aéreos não tripulados baseado em blockchain e smart contract - Moreira, Letícia D Santi (2022)
This final paper presents an architecture proposal and development of delivery system with unmanned aerial vehicles based on Blockchain and Smart Contract.This system integrates the Ethereum Blockchain, the simulation environment Gazebo and the flight controller PX4.The system implementation is divided into three applications developed using Python programming language. One aplication is used to define the Smart Contract in Solidity and deploy it in the Blockchain. The second one integrates Smart Contract and the unmanned aerial vehicle. The last one allows the delivery requests to the Smart Contract. The PX4 is simulated using the software-in-the-loop technique, receiving flight missions for deliveries and controlling the vehicle to delivery point. The Ganache CLI tool is used to emulate a local Ethereum Blockchain. Gazebo is used to simulate the deliveries inside the San Carlos airport environment, United States, and the unmanned aerial vehicle, Thypon H480.